2015
DOI: 10.1088/1367-2630/17/2/023033
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic emission of neutral atoms: evidence of an anisotropic Rydberg sheath in nanoplasma

Abstract: Intense laser-produced plasma is a complex amalgam of ions, electrons and atoms both in ground and excited states. Little is known about the spatial composition of the excited states that are an integral part of most gaseous or cluster plasma. In cluster-plasma, Rydberg excitations change the charge composition of the ions through charge transfer reactions and shape the angular distributions. Here, we demonstrate a non-invasive technique that reveals the anisotropic Rydberg excited cluster sheath by measuring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In our earlier experiments, we demonstrated that neutralatom emission is more anisotropic than the positive-ion emission from single-cluster explosions [15]. A priori, one would expect that the anisotropy in the negative-ion emission should be more than that of neutrals, since anions are formed from a further electron-transfer reaction that reduces the neutral atoms.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…In our earlier experiments, we demonstrated that neutralatom emission is more anisotropic than the positive-ion emission from single-cluster explosions [15]. A priori, one would expect that the anisotropy in the negative-ion emission should be more than that of neutrals, since anions are formed from a further electron-transfer reaction that reduces the neutral atoms.…”
Section: Resultsmentioning
confidence: 84%
“…Recently, experiments carried out nearly at 100 times larger cluster densities, where the spatial extent of the cluster jet is also much larger than the laser focus, have revealed hitherto unanticipated intracluster dynamics [12][13][14][15][16]. It was found that while the ion energies change very little, the ion charge states, as observed in Thompson parabola spectrometry [17], are reduced to an anomalously low value [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Krishnmaurthy [L-I27] reported on the acceleration of neutral atoms in laserproduced plasmas. It was shown that laser plasma ion accelerators can be converted to compact-efficient MeV neutral atom accelerators (Rajeev et al 2013(Rajeev et al , 2015Malay et al 2017). In particular, with nanocluster exposed to intense laser pulses, it is possible to convert more than 90% of the accelerated ions to neutral atoms.…”
Section: Laser-driven Ion Acceleration and Applicationsmentioning
confidence: 99%